Pengelolaan Sumber Daya Alam Perspektif Al-Qur’an - N, Nurjannah; M, Misbahuddin; Ridwan, Saleh (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The management of natural resources has been ordered by Allah in the Qur'an so that humans can fulfill their daily needs. Both individuals and the general public, all have the right to utilize the natural resources on earth within certain limits while remaining aware that Allah swt. is the absolute owner of everything in this world. Natural resources are everything that comes from nature to meet human needs. Natural resources are something that can be utilized for various interests and needs of human life so that they can live more prosperously in our natural environment. This universe was created by Allah swt. very perfect. To regulate the continuity of life of his creatures on earth, Allah swt. has given trust to humans to prosper and manage it in a good way so that there is no damage on the earth.